Inherited Factor XII Deficiency—What Is the Real Concern for Neuroanesthesiologist: Bleeding or Clotting - Mouleeswaran Sundaram (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Factor XII deficiency is a rare disorder that can complicate the perioperative management of a patient. Factor XII plays an important role in the activation of intrinsic pathway of coagulation; the deficiency, therefore, results in prolongation of activated partial thromboplastin time (aPTT). This aPTT prolongation is expected to cause increased bleeding during surgery. However, on the contrary, in vivo isolated factor XII deficiency is associated with increased risk of thromboembolism (this risk being higher than the risk of bleeding). We report the perioperative management of a patient with factor XII deficiency who underwent cervical vertebral fusion (C1–C2) for atlantoaxial dislocation.